Determination of mean shear wave velocity to 30 m depth for site classification using shallow depth shear wave velocity profile in Korea. Issue 73 (June 2015) - Sun, Chang-Guk
Abstract: The mean shear wave velocity to a depth of 30 m ( V S 30), established in the western United States, is the current site classification criterion for determining the seismic design ground motion, taking site amplification potential account into. To evaluate V S 30 at a site, a shear wave velocity ( V S ) profile extending to a depth of at least 30 m must be acquired using in situ seismic tests. In many cases, however, the obtained V S profile does not extend to a depth of 30 m due to unfavorable field conditions and limitations of testing techniques. In this study, V S 30 and the mean shear wave velocity to depths less than 30 m ( V S Ds ) were calculated using V S profiles of more than 30 m obtained by seismic tests at 72 sites in Korea, and the correlation between V S 30 and V S Ds was drawn based on the computed mean V S data. Additionally, a method for extrapolating the V S profile from shallow depths to 30 m and bedrock was developed by building a shape curve based on the average data of all V S profiles. These two methods of extrapolating V S 30 from shallow V S profiles, using V S Ds and a shape curve, resulted in less bias than the simple method in which the lowermost V S value obtained is extended to the depth of 30 m. These two extrapolation methods are useful for V S profiles extending to depths of at least 10 m. Furthermore, the shape curve method developed in this study may be useful in the western United States as well as in Korea. Highlights: Extensive in-situ seismic tests to obtain VS profiles were performed in Korea. Geotechnical parameters, VS 30 and TG, were compared between Korea and western US. The correlation between VS 30 and shallow mean VS was derived for site classification. The shape curve of VS with depth was suggested to determine earthquake ground motion.